COSHER joint industry project: Large scale pipeline rupture tests to study CO2 release and dispersion. (June 2015) - Ahmad, Mohammad; Lowesmith, Barbara; De Koeijer, Gelein; Nilsen, Sandra; Tonda, Henri; Spinelli, Carlo; Cooper, Russell; Clausen, Sigmund; Mendes, Renato; Florisson, Onno
Highlights: A CO2 pipeline rupture experiment was carried out. Fast pressure drop in test rig is observed followed by long saturation phase. The resulting visible CO2 cloud reached about 400 m from the rupture location. This large scale test could be used for discharge and dispersion model validation and for risk analyses of CO2 pipeline. Abstract: The COSHER joint industry project involved the conduct of large scale experiments to provide release and dispersion data under well-defined conditions, studying the full bore rupture of a CO2 dense phase high pressure underground pipeline at large scale. The data generated are useful for model development and validation as well as for better understanding of the risks due to large scale underground CO2 pipeline ruptures. In order to simulate the depressurization of a pipeline, a 219.1 mm diameter pipeline loop was fed from both ends by a 148 m 3 reservoir of CO2 . The rig was designed to promote outflow in the liquid phase for as long as possible. About 136 ton of CO2 were released in 204 s. During the experiments, measurements of the fluid pressure, fluid temperature and wall temperature of the test facility were made together with measurements of the CO2 concentration contours and temperature within the dispersing gas cloud.